Substance use before or during pregnancy and the risk of child mortality, perinatal morbidities and congenital anomalies - Charles Tzu-Chi Lee; Vincent Chin-Hung Chen; Johnny Kuang-Wu Lee; Shu-I Wu; Gillian Cheng; Tzu-Min Kao; Shih-Yuan Wang; Michael Gossop (Cambridge University Press, 2023)
Abstract Aims We aimed to investigate child mortality, perinatal morbidities and congenital anomalies born by women with substance misuse during or before pregnancy (DP or BP). Methods Taiwan Birth Registration from 2004 to 2014 linking Integrated Illicit Drug Databases used to include substance misuse participates. Children born by mothers convicted of substance misuse DP or BP were the substance-exposed cohort. Two substance-unexposed comparison cohorts were established: one comparison cohort selected newborns from the rest of the population on a ratio of 1:1 and exact matched by the child's gender, child's birth year, mother's birth year and child's first use of the health insurance card; another comparison cohort matched newborns from exposed and unexposed mothers by their propensity scores calculated from logistic regression. Results The exposure group included 1776 DP, 1776 BP and 3552 unexposed individuals in exact-matched cohorts. A fourfold increased risk of deaths in children born by mothers exposed to substance during pregnancy was found compared to unexposed group (hazard ratio [HR] = 4.54, 95% confidence interval (CI): 2.07-9.97]. Further multivariate Cox regression models with adjustments and propensity matching substantially attenuated HRs on mortality in the substance-exposed cohort (aHR = 1.62, 95% CI: 1.10-2.39). Raised risks of perinatal morbidities and congenital anomalies were also found. Conclusions Increased risks of child mortality, perinatal morbidities or congenital anomalies were found in women with substance use during pregnancy. From estimates before and after adjustments, our results showed that having outpatient visits or medical utilizations during pregnancy were associated with substantially attenuated HRs on mortality in the substance-exposed cohort. Therefore, the excess mortality risk might be partially explained by the lack of relevant antenatal clinical care. Our finding may suggest that the importance of early identification, specific abstinence program and access to appropriate antenatal care might be helpful in reducing newborn mortality. Adequate prevention policies may be formulated.